Diamond Photoconductive Antenna for Terahertz Generation Equipped with Buried Graphite Electrodes - Taras Viktorovich Kononenko; Kuralai Khamitzhanovna Ashikkalieva; Vitali Viktorovich Kononenko; Evgeny Viktorovich Zavedeev; Margarita Alexandrovna Dezhkina; Maxim Sergeevich Komlenok; Evgeny Evseevich Ashkinazi; Vladimir Valentinovich Bukin; Vitaly Ivanovich Konov (Photonics, 2023)
It has been shown recently that a photoconductive antenna (PCA) based on a nitrogen-doped diamond can be effectively excited by the second harmonic of a Ti:sapphire laser (λ = 400 nm). The THz emission performance of the PCA can be significantly increased if a much stronger electric field is created between the close-located electrodes. To produce a homogeneous electric field over the entire excited diamond volume, the laser fabrication of deep-buried graphite electrodes inside the diamond crystal was proposed. Several electrodes consisting of the arrays of buried pillars connected by the surface graphite stripes were produced inside an HPHT diamond crystal using femtosecond and nanosecond laser pulses. Combining different pairs of the electrodes, a series of PCAs with various electrode interspaces was formed. The THz emission of the PCAs equipped with the buried electrodes was measured at different values of excitation fluence and bias voltage (DC and pulsed) and compared with the emission of the same diamond crystal when the bias voltage was applied to the surface electrodes on the opposite faces. All examined PCAs have demonstrated the square-law dependencies of the THz fluence on the field strength, while the saturation fluence fluctuated in the range of 1200–1600 µJ/cm2. The THz emission performance was found to be approximately the same for the PCAs with the surface electrodes and with the buried electrodes spaced at a distance of 1.4–3.5 mm. However, it noticeably decreased when the distance between the buried electrodes was reduced to 0.5 mm.